Insights Gained From the Study of Pediatric Systemic Lupus Erythematosus - Lo, Mindy S. (Frontiers in Immunology, 2018)
The pathophysiology of systemic lupus erythematosus (SLE) has been intensely studied but remains incompletely defined. Currently, multiple mechanisms are known to contribute to the development of SLE. These include inadequate clearance of apoptotic debris, aberrant presentation of self nucleic antigens, loss of tolerance and inappropriate activation of T and B cells. Genetic, hormonal, and environmental influences are also known to play a role. The study of lupus in children, in whom there is presumed to be greater genetic influence, has led to new understandings that are applicable to SLE pathophysiology as a whole. In particular, characterization of inherited disorders associated with excessive type I interferon production has elucidated specific mechanisms by which interferon is induced in SLE. In this review, we discuss several monogenic forms of lupus presenting in childhood and also review recent insights gained from cytokine and autoantibody profiling of pediatric SLE.